Effecting Compulsory Acquisition via the Amalgamation Procedure in Singapore - WAN, Wai Yee (Institutional Knowledge at Singapore Management University, 2007)
Sections 215A to 215J of the Companies Act were enacted to facilitate the amalgamation or merger of Singapore companies. These provisions also enable an acquiror to achieve full ownership of the target company by indirectly buying out the shares held by minority shareholders, even if such shareholders have voted against the amalgamation at the shareholders' meeting. This author argues that the amalgamation procedure, as compared with the other forms of compulsory acquisition, may have the unintended effect of unduly favouring the majority shareholders at the expense of the minority shareholders. The problem is partially mitigated by the fact that the provisions allow for shareholders to apply to the court for relief if the amalgamation would lead to unfair prejudice. Alternatively, shareholders may bring a petition under section 216 of the Companies Act, on the ground that the amalgamation is oppressive, unfairly discriminatory or otherwise prejudicial to their interests. This article explores the circumstances in which the court would intervene and it is argued that the basis of any intervention is to ensure that the requisite shareholder approval is fairly obtained.